Traditional Chinese exercise for sleep problems in healthy adults and patients: a systematic review and meta-analysis of randomized controlled trials (The Journal of the International Society of Chinese Health Practices, 2021)
Background Adequate sleep is an essential factor contributing to mental and physical health. Because of changes in lifestyle and the aging process, sleep problems have worsened. However, to our knowledge, there have been no systematic reviews summarizing the effects of traditional Chinese exercise (Tai Chi, Qi Gong, Baduanjin, Wuqinxi, Liuzijue, and Daoyin) on sleep problems among any diagnostic population. Objectives This systematic review and meta-analysis were performed to systematically evaluate the evidence on the effects of traditional Chinese exercise on sleep problems. Methods Six databases were systematically searched for randomized controlled trials (RCT) with any type of traditional Chinese exercise for sleep problems in healthy adults and patients. The search deadline was from database inception to October 16, 2019. Outcomes were self-reported or objective sleep measurements. The Cochrane risk assessment tool was used to assess the quality of the included literature. The standardized mean difference (SMD) was calculated using random-effects models. Results The meta-analysis included 13 studies that assessed the Pittsburgh Sleep Quality Index (PQSI), showing that the experimental group had better global sleep quality than the control group. Conclusions Traditional Chinese exercise can effectively improve sleep quality. Tai Chi and Qi Gong programs are more effective for treating sleep problems, and subjects with illness may receive more benefit than healthy subjects and those with insomnia. Tai Chi and Qi Gong programs that are 8-12 weeks long, for 120-300 min every week, are effective for treating sleep problems.